Moving around is no excuse be idle in gaining knowledge, Aimi receives Srikandi Matahari Award - Nur Hartini, Mohd Hatta (UMPSA, 2023)
GAMBANG, 21 October 2023 - Ever since she was a kid, her family has always moved around due to the demands of her mother’s job as a teacher in Tawau, Sabah.